Influencing of serum inflammatory factors on IVF/ICSI outcomes among PCOS patients with different BMI - He, Yilei; Li, Rong; Yin, Jingwen; Yang, Zi; Wang, Yuanyuan; Chen, Lixue; Yang, Shuo; Qiao, Jie (Frontiers in Endocrinology, 2023)
Overweight and obese are important factors leading to the occurrence of long-term complications in women with polycystic ovary syndrome (PCOS). There has been controversy over whether dissatisfaction with pregnancy outcomes in PCOS patients is influenced by chronic inflammatory status or obesity. This retrospective study analyzed the levels of inflammatory factors in PCOS patients with different body mass index (BMI) groups and effective predictors of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) pregnancy outcomes. There were 273 women with PCOS diagnosed who completed serum inflammatory factors test between January 2017 and June 2022 were selected. The data of 7,649 infertility PCOS patients who received their first IVF/ICSI treatment in the Reproductive Center of Peking University Third Hospital during the period of the study were collected. Finally, 92 PCOS patients were included in the high BMI group, while 97 patients were included in the normal BMI group. Baseline characteristics were collected and the pregnancy outcomes were compared among the two groups. Then, serum inflammatory factors' effect on IVF/ICSI pregnancy outcomes were analyzed with age, anti-Mullerian Hormone (AMH) and BMI adjusted. PCOS patients in the high BMI group significantly had a lower number of oocytes retrieved and good quality embryos. The high BMI group PCOS patients had higher levels of IL-6 and lower cumulative clinical pregnancy and live birth rates. The level of GM-CSF was higher in the first cycle transfer and cumulative miscarriage group. High TNF-α was negatively correlated with the first transfer cycle and cumulative clinical pregnancy rates after age, AMH and high BMI adjusted. In addition, the cumulative live birth rate was negatively correlated with high IL-6, but the first cycle transfer and cumulative live birth rates were positively correlated with high IL-1β. For PCOS patients, in addition to BMI, attention should also be paid to inflammatory indicators.High levels of TNF-α and IL-6 were negatively correlated with pregnancy outcomes, but high IL-1β was positively correlated with live birth rates among PCOS patients. The level of GM-CSF was higher in miscarriage PCOS patients.